Patiromer for the management of hyperkalemia in heart failure with reduced ejection fraction: the DIAMOND trial - Butler, Javed; Anker, Stefan D; Lund, Lars H; Coats, Andrew J S; Filippatos, Gerasimos; Siddiqi, Tariq Jamal; Friede, Tim; Fabien, Vincent; Kosiborod, Mikhail; Metra, Marco; Piña, Ileana L; Pinto, Fausto; et al. (European heart journal, 2022)
AIMS: To investigate the impact of patiromer on the serum potassium level and its ability to enable specified target doses of renin-angiotensin-aldosterone system inhibitor (RAASi) use in patients with heart failure and reduced ejection fraction (HFrEF). METHODS AND RESULTS: A total of 1642 patients with HFrEF and current or a history of RAASi-related hyperkalemia were screened and 1195 were enrolled in the run-in phase with patiromer and optimization of the RAASi therapy [≥50% recommended dose of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker/angiotensin receptor-neprilysin inhibitor, and 50 mg of mineralocorticoid receptor antagonist (MRA) spironolactone or eplerenone]. Specified target doses of the RAASi therapy were achieved in 878 (84.6%) patients; 439 were randomized to patiromer and 439 to placebo. All patients, physicians, and outcome assessors were blinded to treatment assignment. The primary endpoint was between-group difference in the adjusted mean change in serum potassium. Five hierarchical secondary endpoints were assessed. At the end of treatment, the median (interquartile range) duration of follow-up was 27 (13-43) weeks, the adjusted mean change in potassium was +0.03 mmol/l in the patiromer group and +0.13 mmol/l in the placebo group [difference in the adjusted mean change between patiromer and placebo: -0.10 mmol/l (95% confidence interval, CI -0.13, 0.07); P < 0.001]. Risk of hyperkalemia >5.5 mmol/l [hazard ratio (HR) 0.63; 95% CI 0.45, 0.87; P = 0.006), reduction of MRA dose (HR 0.62; 95% CI 0.45, 0.87; P = 0.006), and total adjusted hyperkalemia events/100 person-years (77.7 vs. 118.2; HR 0.66; 95% CI 0.53, 0.81; P < 0.001) were lower with patiromer. Hyperkalemia-related morbidity-adjusted events (win ratio 1.53, P < 0.001) and total RAASi use score (win ratio 1.25, P = 0.048) favored the patiromer arm. Adverse events were similar between groups. CONCLUSION: Concurrent use of patiromer and high-dose MRAs reduces the risk of recurrent hyperkalemia (ClinicalTrials.gov: NCT03888066).
Keywords: draslík; Hyperkalemia; srdeční selhání; hyperkalemie; Renin-Angiotensin System; lidé; Mineralocorticoid Receptor Antagonists; Potassium; antagonisté mineralokortikoidních receptorů; renin-angiotensin systém; tepový objem; Humans; Heart Failure; Stroke Volume